Hearing Spiritual Voices Medieval Mystics, Meaning and Psychiatry - Cook, Christopher C.H (Bloomsbury Academic, 2023)
This open access book explores unusual perceptual, or perception-like, experiences. These are often meaningful to those who have them and may be sympathetically or unsympathetically interpreted by others. One interpretation, especially when voices are associated with unusual behaviour, is that they are evidence of mental disorder. Ostensibly such interpretations are sympathetic (showing concern for someone who is ill) but in practice they are used to deny the meaning and value of the experiences for those concerned, thus depriving them (and others) of creative and innovative ways of understanding the human condition. The question is thus one of the meaning. Are such experiences meaningful only as indicators of a diagnosis, or are they meaningful in other ways, shedding light on human self-understanding and perhaps even a wider spiritual reality? Psychiatry has tended to see such phenomena as diagnostically meaningful but not as sources of deeper insight into the human condition. This book takes three 14th century examples of women who heard spiritually significant voices: Margery Kempe, Julian of Norwich, and Joan of Arc. Each of these women, in different ways, has left an enduring legacy in literature and history. Modern psychiatric commentary on the voices that they reported has generally focussed on diagnosis rather than on wider questions of meaning. These commentaries will be used as a lens through which to consider how contemporary psychiatric practice might be enriched by the humanities and enabled to find a more spiritually empathetic, if not also sympathetic, enriching and meaning enhancing perspective on unusual mental phenomena. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The Wellcome Trust.